A novel Salvialactomine from the callus culture of Salvia santolinifolia Boiss. Issue 7 (3rd April 2018) - Jan, Tour; Qadri, Raiha; Naqvi, Beena; Adhikari, Achyut; Nadeem, Said; Muhammad, Akhtar
Abstract: A novel compound Salvialactomine (1 ) along with two other unusual occurring natural products Pentatriacontanoic acid 1, 3-dihydroxypropyl ester (2 ) and 5-Methylflavone (3 ) were isolated from the callus of Salvia santolinifolia Boiss. Callus was initiated on MS medium containing NAA (0.5 mg/L) and further sub-cultured on MS medium supplemented with NAA with BA (0.5 + 1.5 mg/L). The structures of isolated compounds were determined by using mass spectrometry, 1D, and 2D–NMR techniques. Compounds1, and3 were tested for two different cancer cell lines, i.e. Hela (Cervical cancer cell) and PC-3 (Prostate cancer cells). IC50 was found as > 30 using Doxorobicin (0.912 ± 0.12 μmol L −1 ) as a standard. Abstract :